Estudo geoambiental das microbacias do córrego Tanquinho e do córrego do Serralha no município de Araraquara-SP - Assalve, Layla Cristina de Freitas (2023)
In recent decades, urban acceleration due to market speculation has led to situations of imbalance between the environment and the anthropic environment. The implementation of human activities in a peri-urban environment without proper planning affects the natural balance of river basins, which play an important role in supplying water to urban areas, impacting the distribution capacity and water quality. The objective of this research was to carry out a Geoenvironmental Study of the micro-basins of the Tanquinho stream and the Serralha stream in the municipality of Araraquara-SP, so that technical contributions guide decision-making in conducting urban development compatible with sustainable development and the protection of water resources. A diagnosis of geoenvironmental units was carried out using cartographic products that were integrated into a GIS environment, generating a summary cartographic document: Map of Geoenvironmental Units at a scale of 1:20,000. Carrying out the Geoenvironmental Study based on the spatial intersection operation proved to be efficient, allowing the geoenvironmental attributes to be analyzed and correlated in an integrated manner. The compartmentalization of the microbasins resulted in thirteen homogeneous Geoenvironmental Units considering the influences of variables on water resources. The different classes of uses, together with the relief forms and unconsolidated materials, have different influences on the water resources of the Tanquinho and Serralha streams in terms of water accumulation in the drainage, favoring subsurface exfiltration. The slope classes and the greater or lesser waterproofing of the soil influence the surface water runoff or the infiltration of water into the underground layers. From the analyzes it was found that it is necessary to adopt management practices that do not increase waterproofing, that increase infiltration rates and reduce surface water runoff, in addition to means of soil recovery and protection of springs, especially in Units 2, 4, 6, 7, 8 and 10, which already suffer from degradation in water resources.